The Influence Of Managerial Ownership, Return On Assets, Company Size, And Debt To Equity On Company Value: (Case Study On Financials Sector Companies For The 2021-2022 Period) - Nugroho, Raffindra Gustriadhi; Muid, Dul (Politeknik Negeri Ambon, 2024)
The background of the problem in this study is that the company is still unable to increase profits continuously which results in the company’s value still often decreasing. This study aims to determine the effect of Managerial Ownership, Return on Assets (ROA), Company Size, and Debt to Equity Ratio (DER) on Company Value in Indonesia on financial sector companies listed on the Indonesia Stock Exchange for the 2021-2022 period. The purposive sampling method was used in this study to select company samples that fit the criteria in the study with a total of 50 samples. The result of analysis that has been conducted in this study show that managerial ownership cannot affect the value of the company, while return on assets (ROA) and debt to equity ratio (DER) have positive influence on company value. Which can be interpreted that every increase in return on assets (ROA) and debt to equity ratio (DER) then the company’s value will also increase. In addition, it was found that the size of the company has a negative influence on the value of the company, so that every time the size of the company increases, the value of the company decreases.